anonymous
  • anonymous
solve for x 6-3(2x-4)=2(1+x)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Solve for x: 6 x-3 (2 x-4) = 2 (x+1) Factor the polynomial, 2 x-4. Factor 2 from the polynomial 2 x-4: 6 x-3×2 (x-2) = 2 (x+1) Multiply -3 and 2 together. -3×2 = -6: 6 x+-6 (x-2) = 2 (x+1) Distribute -6 over x-2. -6 (x-2) = 12-6 x: 6 x+12-6 x = 2 (x+1) Group like terms in 6 x+12-6 x. Grouping like terms, 6 x+12-6 x = 12+(6 x-6 x): 12+(6 x-6 x) = 2 (x+1) Look for two terms that sum to zero. 6 x-6 x = 0: 12 = 2 (x+1) Reverse the equality in 12 = 2 (x+1) in order to isolate x to the left hand side. 12 = 2 (x+1) is equivalent to 2 (x+1) = 12: 2 (x+1) = 12 Divide both sides by a constant to simplify the equation. Divide both sides of 2 (x+1) = 12 by 2: (2 (x+1))/2 = 12/2 Any nonzero number divided by itself is one. 2/2 = 1: x+1 = 12/2 Reduce 12/2 to lowest terms. The gcd of 12 and 2 is 2, so 12/2 = (2×6)/(2×1) = 2/2×6 = 6: x+1 = 6 Isolate terms with x to the left hand side. Subtract 1 from both sides: x+(1-1) = 6-1 Look for two terms that sum to zero. 1-1 = 0: x = 6-1 Evaluate 6-1. 6-1 = 5:
anonymous
  • anonymous
x6-3*(2*x-4)=2*(1+x) simplifies to x6-8*x+10=0

Looking for something else?

Not the answer you are looking for? Search for more explanations.